DIGITALIZATION OF HEALTH CARE SERVICES – CASE OF GERMANY - Sofija Nikolić Popadić (Glasnik Advokatske komore Vojvodine, 2020)
Digitization of health care services brings many challenges. The process of introducing new technologies can be very long and relatively complicated. Changes that affect the whole system inevitably affect the relationship between physicians and patients, especially with regard to new ways of communicating and providing health services. The research is dedicated to the process of digitization of health care services in Germany, as one of the leading European countries in terms of financial allocations for health care and the availability of health care services. The research is analyzing problems that have arisen in the process of digitalization and the potential solutions. Special attention was dedicated to legal regulations in this field. In addition to the need for frequent adaptation of legal regulations, the example of Germany shows that it is crucial to achieve the appropriate level of security and trust of users and service providers in the new system in order to make its implementation in practice more effective. The paper also shows the latest innovations in this field, which implementation can be expected in other countries in the next period. The new digitalization measures will also be a challenge for lawyers who will have a task to adapt regulations to new needs and to find innovative solutions.